Memimpikan Museum yang Menarik Pengunjung - Baskoro Daru Tjahjono (Balai Arkeologi Sumatera Utara, 2010)
AbstractActually, the presence of museums in Indonesia has been quite a long time. From time to time, the museum has been progressing, both qualitatively and quantitatively. The main purpose of the museum is for fun and learning for the community. But until now, most of the museums in Indonesia have not been able to attract many visitors. In general, the Indonesian people are still as consumers or spectators. Therefore, to attract visitors, the museum should be made as attractive as possible, building, exhibition layout, lighting, equipment room and the attractions.